A study of levothyroxine substitution therapy on subclinical hypothyroid patients and its effects on lipid profile in the department of medicine at tertiary care hospital - Raut, Binod; Paudel, N; Bhosekar, N (Journal of Diabetes and Endocrinology Association of Nepal, 2020)
Background: Subclinical hypothyroidism is represented by high serum thyroid stimulating hormone (TSH) and normal serum free T4 and T3, Recent studies on subclinical hypothyroidism and lipid profile indicates that the serum total cholesterol, LDL-C, and total triglycerides were significantly increased. Clinical evidence suggests that thyroid replacement therapy with levothyroxine has beneficial effect. Methods: It is a hospital based prospective observational study involving 122 patients based on non probability sampling conducted in the Department of Internal Medicine. The study involved patients who have been diagnosed with subclinical hypothyroidism with normal level of free T4, T3 and elevated levels of TSH with positive Thyroperoxidase (TPO) antibodies. Patients were advised to investigate lipid profile before and after prescribing levothyroxine. Follow up was done after 6-9 wks. Results: In this study 122 patients diagnosed with Subclinical hypothyroidism were prescribed with levothyroxine in which 112 came for follow up. The mean age of the patient was 46.81. There was significant reduction in mean TSH from 12.09 (±1.89)mIU/L to 7.97(±1.59)mIU/L,TC from 217.12( ±20.87)mg/dl to 198.47( ±17.34)mg/dl and LDL from 137.16(±14.57)mg/dl to 124.62( ±12.89)mg/dl was found along with significant reduction in VLDL was found after levothyroxine therapy, There was slight reduction in serum triglyceride was found with no significant alteration in HDL and BMI levels. Conclusion: The study showed significant reduction in the lipid profile including TC, LDL and VLDL after levothyroxine therapy. There was significant reduction in the level of TSH was also found whereas the level of free T4 and T3 were not much altered. There was no significant change found in the level of HDL and BMI.